Pre-service teachers' learning of diagnostic skills in a video-based simulation: Effects of conceptual vs. interconnecting prompts on judgment accuracy and the diagnostic process. (February 2023) - Sommerhoff, Daniel; Codreanu, Elias; Nickl, Michael; Ufer, Stefan; Seidel, Tina
Abstract: Video-based simulations are considered authentic approximations of practice that can support pre-service teachers' acquisition of diagnostic skills. Still, there is insufficient knowledge on the (differential) effectiveness of different types of prompts on learning in such environments. The presented study experimentally compared the effects of two types of prompts on participants' judgment accuracy and diagnostic processes in a video-based simulation for diagnostic skills in the context of secondary mathematical argumentation skills. The prompts focused learners either on one indicator of argumentation skills (conceptual prompts) or two indicators and their relation (interconnecting prompts). Results indicate that the prompts effectively supported learning in short interventions. While conceptual prompts led to generally higher learning, interconnecting prompts showed a differential effectiveness based on prior knowledge. Besides highlighting a prototypical video-based simulation for diagnostic skills and prompts to support these, results give indications for teaching diagnostic skills and the adaptive use of prompts for simulation-based learning. Highlights: Simulations can help to acquire diagnostic skills in pre-service teacher education. Different types of prompts have a differential impact on learning in simulations. Conceptual prompts lead to learning gains independent of learners' prior knowledge. The effects of advanced interconnecting prompts are dependent on learners' pedagogical content knowledge (PCK). Results are essential for adaptive simulation-based learning in teacher education.